Relationship between California Mastitis Test score and ultrasonographic teat measurements in dairy cows - Seker, I.; Risvanli, A.; Yuksel, M.; Saat, N.; Ozmen, O. (Wiley, 2009)
Objective The majority of published studies about mastitis are related to the control and prevention of mastitis, with particular emphasis on eliminating predisposition factors. The objective of the current study was to determine the role of teat morphology as an important factor in the aetiology of mastitis. Design Ultrasonographic measurements were taken from 190 teats from 100 dairy cows of different breeds. Procedure Mastitis in cows was diagnosed by the California Mastitis Test (CMT) and microbiological tests. The data were evaluated in the light of the clinical history of the animals. Results Main effects of breed on teat diameter at the position of the Furstenberg rosette (FTD) and teat cistern diameter (CD), that of age on FTD and overall teat diameter (OTD), and that of CMT score on CD and OTD were significant (P < 0.05, P < 0.01). Number of lactations, pregnancy, the lactation period and the udder lobe (rear, front) were not found to have a significant effect on any of the measurements. Results showed that CD was significantly smaller (1.44 + 0.04 cm) (P < 0.01) in CMT-positive udder lobes than that in CMT-negative lobes. No difference was detected in canal length, CD, teat wall thickness, OTD or FTD between the CMT-positive and -negative lobes. Conclusion The occurrence of mastitis could be related to specific ultrasonographic teat measurements (e. g. CD, OTD and FTD) and these may be important in the breeding of cows with a predisposition to mastitis, as well in the evaluation of in-herd cows in terms of udder/teat deformities.
Keywords: dairy cattle; mastitis; teat measurements; ultrasonography